A study on the problems of the usage of incinerators in Malaysia / Muhamad Rosli Sulaiman ... [et al.] - Sulaiman, Muhamad Rosli; Syed Abdul Kadir, Sharifah Aishah; Ibrahim, Ruhani; Husin, Maryam (Institute of Research, Development and Commercialisation (IRDC), 2007)
Incineration is one of the options available to dispose municipal solid wastes (MSW) as it is capable of breaking down hazardous non-metallic wastes besides destroying bacteria and viruses. In terms of volume of wastes, incineration can reduce almost instantaneously by 90 %. In 1998, the government of Malaysia embarked on a pilot project to use incinerators to dispose MSW in four popular resort islands to see the effectiveness of this technique of waste disposal. Seven units of mini incinerators were installed on the islands and the local municipals were made responsible to manage and maintain.This project looked into the problems arises when incineration is used for MSW disposal on these islands. Data collected revealed that the plants were not properly managed and maintained. This was due to the lack of funds available for effective and smooth operation and the absence of highly expert personnel required to maintain the plant. Other factors that contribute to the inefficiency are inadequate air pollution control facilities and the infrastructure which do not condon the foul odour. Further research work need to be done to monitor the operation of these incinerators in order to explore its potential to dispose waste safely, effectively and cleanly.